Problematising the compatibility of islam and democracy through a hermeneutical approach - BAYRAM, AHMET KEMAL (Rowman & Littlefield, Oxford, 2023)
A contest is afoot in Muslim discourses around the world in the twenty-first century. Prevalent norms and acts are subject to competing motivations, trends and forces. The image of a monolithic Islam is thus wholly inadequate to identify and interpret the different expressions of Muslim thought and practice in their specific yet connected contexts. This book proposes competing and persuasive perspectives for interpreting what Muslims say, do and think in collective settings or in the light of common frames of reference. The chapters contained in this book reflect a diversity of disciplines and interests. Nonetheless, a common thread of the preoccupation with meanings in context unites the contributors and the approaches to their chosen examples. Islam is not a discrete category that is taken for granted. Instead, the cacophony of voices in the Muslim world situated in specific contexts, variously national, regional or global, is allowed to inform each chapter. Here one encounters contemporary Muslims participating in discourses with a contested character that create opportunities to augment or question orthodox dictates or transmit or alter existing beliefs and practices. What emerges are nuanced portraits of contemporary Muslim thought and practice that reveal a far from monolithic Islam to which all things Islamic can be reduced.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Social Sciences and Humanities; Political Science; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities